Respuestas
Respuesta dada por:
0
a) ![4 x^{3} -8 x^{2}y -4x y^{2} -32b x^{2} =
-( 8 x^{2} y+4x y^{2} ) +( 4x^{3} -32b x^{2}) 4 x^{3} -8 x^{2}y -4x y^{2} -32b x^{2} =
-( 8 x^{2} y+4x y^{2} ) +( 4x^{3} -32b x^{2})](https://tex.z-dn.net/?f=4+x%5E%7B3%7D+-8+x%5E%7B2%7Dy+-4x+y%5E%7B2%7D+-32b+x%5E%7B2%7D+%3D+%0A-%28+8+x%5E%7B2%7D+y%2B4x+y%5E%7B2%7D+%29+%2B%28+4x%5E%7B3%7D+-32b+x%5E%7B2%7D%29+)
![-( 8 x^{2} y+4x y^{2} ) +( 4x^{3} -32b x^{2}) =
-4xy(x+4y) + 4 x^{2} ( x -8b) =
(-4xy+4x)(x+4y)(x-8b) -( 8 x^{2} y+4x y^{2} ) +( 4x^{3} -32b x^{2}) =
-4xy(x+4y) + 4 x^{2} ( x -8b) =
(-4xy+4x)(x+4y)(x-8b)](https://tex.z-dn.net/?f=-%28+8+x%5E%7B2%7D+y%2B4x+y%5E%7B2%7D+%29+%2B%28+4x%5E%7B3%7D+-32b+x%5E%7B2%7D%29+%3D%0A%0A-4xy%28x%2B4y%29+%2B+4+x%5E%7B2%7D++%28+x+-8b%29+%3D%0A%0A%28-4xy%2B4x%29%28x%2B4y%29%28x-8b%29)
Obten el termino que se repite en todas y lo restas [/tex]
b)
[/tex]
c)![100 x^{4} -49 = (10 x^{2} +7)(10 x^{2} -7) 100 x^{4} -49 = (10 x^{2} +7)(10 x^{2} -7)](https://tex.z-dn.net/?f=100+x%5E%7B4%7D+-49+%3D+%2810++x%5E%7B2%7D+%2B7%29%2810++x%5E%7B2%7D+-7%29)
d)![64 x^{3} -27 = (4x -3)(16 x^{2} +12x+9) 64 x^{3} -27 = (4x -3)(16 x^{2} +12x+9)](https://tex.z-dn.net/?f=64+x%5E%7B3%7D+-27+%3D+%284x+-3%29%2816+x%5E%7B2%7D+%2B12x%2B9%29)
e)![125 y^{6} +8= (5 y^{3}+2)(25 y^{3} -10y+2) 125 y^{6} +8= (5 y^{3}+2)(25 y^{3} -10y+2)](https://tex.z-dn.net/?f=125+y%5E%7B6%7D+%2B8%3D+%285+y%5E%7B3%7D%2B2%29%2825+y%5E%7B3%7D+-10y%2B2%29)
f)![16 y^{4} +1 = (4y^{2} + 2y+1)(4y^{2} - 2y+1) 16 y^{4} +1 = (4y^{2} + 2y+1)(4y^{2} - 2y+1)](https://tex.z-dn.net/?f=16+y%5E%7B4%7D+%2B1+%3D+%284y%5E%7B2%7D++%2B+2y%2B1%29%284y%5E%7B2%7D++-+2y%2B1%29)
g)![x^{9} -1 = (x^{2} -1)( x^{4} +2 x^{2} +1) x^{9} -1 = (x^{2} -1)( x^{4} +2 x^{2} +1)](https://tex.z-dn.net/?f=x%5E%7B9%7D+-1+%3D+%28x%5E%7B2%7D+-1%29%28+x%5E%7B4%7D+%2B2+x%5E%7B2%7D++%2B1%29)
Obten el termino que se repite en todas y lo restas [/tex]
b)
c)
d)
e)
f)
g)
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años